Veronica Mars. The complete first season [videorecording (DVD)] - Bell, Kristen, 1980-; Daggs, Percy; Dunn, Teddy (Warner Home Video, 2013)
In the wealthy, seaside community of Neptune, California, the rich and powerful make the rules. Unfortunately for them, there's Veronica Mars, a smart, fearless 17-year-old apprentice private investigator solving the town's toughest mysteries.